Dark triad personalities, self-control, and antisocial/criminal outcomes in Youth - Pechorro, Pedro (2022)
The Dark Triad composed of psychopathy, Machiavellianism, and narcissism, and also self-control are consistently related to antisocial and criminal externalizing outcomes. In the present study, we examined whether self-control mediates the relationships between the Dark Triad and delinquency, conduct disorder, and crime seriousness outcomes. The sample consisted of 567 adolescents (M = 15.91 years, SD = 0.99 years, range = 14– 18 years) from Portugal. Self-control mediated the association between psychopathy and Machiavellianism (but not narcissism) and self-reported juvenile delinquency, conduct disorder symptoms, and crime seriousness. One reason antisocial/criminal behaviors are common in those characterized by psychopathy and Machiavellianism relates to their deficits in selfcontrol as suggested by general theories. Within the nomological network of dark traits, narcissism appears to have enduring and unmediated associations with externalizing features and conduct problems. Our findings add to the literature modeling the Dark Triad along with self-control to elucidate its contributions to antisocial/criminal outcomes in youth.